Ethnic diversity and attitudes towards redistribution: a review of the literature - Holger Stichnoth; Karine van der Straeten (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
We review the empirical literature that studies the effect of ethnic diversity on the welfare state and on individual attitudes. The outcome variables that we cover in the survey are on the one hand public spending, and on the other hand individual attitudes and behaviour, including charity spending. We also review the fast-growing literature that uses experiments to study the effects of ethnic diversity. Many of these studies have appeared since the pioneering survey by Alesina and La Ferrara (2005a), and have not been covered by a survey before.
Keywords: H53; H55; I38; J15; J61; 330; redistribution; social security; welfare state; immigration; ethnic diversity; survey; Ethnische Beziehungen; Migranten; Multikulturell; Sozialstaat; Einkommensumverteilung; Wohltätigkeit; Meinung; USA; Kanada; Europa